Applications of ontologies in knowledge representation of human perception. (6th February 2014) - Prieto–González, Lisardo; Stantchev, Vladimir; Colomo–Palacios, Ricardo
Information overload is becoming bigger as internet grows. This entails several problems such as difficulty in finding information and redundancy of knowledge. In this paper, a solution of these problems is presented as a global representation of knowledge based on human perception, and modelled by means of ontologies. In this study we present the approach with several advantages as well as some drawbacks related to state of the art technologies.